Effect of process parameters on abrasive contamination during water abrasive jet machining of mild steel - Mohd Ali, Afifah; Khan, Ahsan Ali; Mohammad , Yeakub Ali (Trans Tech Publications, Switzerland, 2011)
In the area of grit blasting, it is well known that microscopically small abrasive debris gets trapped on the surface, and due to impact the grits might cause the surface to fracture and a fraction of it to be embedded. The same problem appears in abrasive water jet (AWJ) machining especially in the so-called deformation wear zone or striation zone. The major aim in this study is to investigate the abrasive contamination on mild steel cutting surface. In the present study mild steel was used as the work material, since it is widely used in many industries. In order to analyze the pattern of the contaminations on the cut surface, the selected process parameters were abrasive flow rate, pressure and work feed rate. Abrasive contamination was measured at different depths along the path of the abrasives. The three selected zones for measuring abrasive contamination at different depths were the primary impact zone, the smoother zone and the deformation wear zone. It was found that contamination at the middle zone, i.e., the smoother zone had the least abrasive contamination while the initial impact zone and the deformation wear zone showed high abrasive contamination. It was also found that a higher pressure reduces abrasive contamination while a higher abrasive flow rate and work feed rate increase abrasive contamination.